Founder of Hasidism a quest for the historical Ba'al Shem Tov - Rosman, Moshe 1949- (The Littman Library of Jewish Civilization, 2014)
Moshe Rosman's award-winning research supplies the history behind the legend of the Ba'al Shem Tov and thus changes the master-narrative of hasidism